The Global Economy at a Crossroads - Köz - gazdaság (Köz-gazdaság)
Review of Economic Theory and Policy (RETP) requested an interview with Professor Dr. Andreas Nölke on the following topics: the current global change of the world economy, the future of the global financial order, China-EU relations, prospects of the German economy and the changes in the dependent market economies of the Visegrad 4. Andreas Nölke is a Professor of Political Science specialising in International Relations and International Political Economy at Goethe University Frankfurt since 2007. He is also a Research Fellow at the Leibniz Institute for Financial Research SAFE. Professor Nölke holds a Master's degree in Public Administration (1988) and a PhD in Political Science (1993, with distinction) from the University of Konstanz. He has held teaching positions at the Universities of Konstanz, Leipzig, Amsterdam (Vrije Universiteit), and Utrecht. Professor Nölke's research focuses on comparative and international political economy, particularly the political economy of emerging markets, financialisation, European economic integration, and populism. He is well-known for his influential work on dependent market economies and state-permeated capitalism, and his publications appear in leading journals such as the Review of International Political Economy, World Politics, and Socio-Economic Review. Beyond academia, Professor Nölke has held consultancy roles for prominent organisations, including the German Agency for Technical Cooperation (GIZ), the European Commission, and the World Bank. Professor Nölke's academic contributions extend to serving as an associate editor for prominent outlets such as Routledge Studies in Globalisation and the Journal of Economic Policy Reform.